Technology adoption among higher education students - Berényi, László; Deutsch, Nikolett (Vezetéstudomány / Budapest Management Review, 2023)
The acceptance of technology is of decisive importance in enhancing diffusion of innovation. Personal opinions and attitudes to technology offer particular foundational points for associated development. This study contributes to greater understanding of factors influencing technology acceptance among higher education students. Findings are based on measuring factors of contribution (optimism, proficiency) and inhibition (dependency, vulnerability) drawn from the technology adoption propensity (TAP) instrument and also by calculating TAP index scores derived from a sample of 873 Hungarian higher education students. Results indicate moderate technology adoption propensity driven by high optimism. Tyes of study (business, engineering, administrative) were used as grouping factors for the analysis. Optimism indicates similar results by criterion of study type, but proficiency in technology use is highest among engineering students. Considering goals of the Hungarian National Digitalization Strategy, targeted training programs and acquisition of more experience are necessary in order to improve proficiency in use of technology.